2022
DOI: 10.3390/w14060951
|View full text |Cite
|
Sign up to set email alerts
|

Integration of a Shallow Soda Lake into the Groundwater Flow System by Using Hydraulic Evaluation and Environmental Tracers

Abstract: Lake Velence is a shallow soda lake whose water level and water quality show a severely deteriorating tendency in recent years. Until recently, the groundwater component in the lake’s water budget has not been taken into consideration. To integrate the lake into the groundwater flow system at the regional scale, methods of “basin hydraulics” were applied. In addition, 17 water samples were collected for δ2H and δ18O, and for ΣU, 226Ra and 222Rn activity measurements to use these parameters as environmental tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Water samples for uranium analysis were collected in 0.25 L PP bottles at fewer sites, altogether 16 sites: 12 springs, 1 creek and 3 locations in Lake Balaton (Figure 5). Total uranium activity, ΣU = 234 U + 235 U + 238 U, was determined by alpha spectrometry using NucFilm discs (see measurement details in Baják et al [11,92] and Surbeck [93]).…”
Section: Results Interpretation and Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…Water samples for uranium analysis were collected in 0.25 L PP bottles at fewer sites, altogether 16 sites: 12 springs, 1 creek and 3 locations in Lake Balaton (Figure 5). Total uranium activity, ΣU = 234 U + 235 U + 238 U, was determined by alpha spectrometry using NucFilm discs (see measurement details in Baják et al [11,92] and Surbeck [93]).…”
Section: Results Interpretation and Comparisonmentioning
confidence: 99%
“…Therefore, evaporated waters, such as lakes and rivers, will plot below the GMWL. Waters infiltrated during different climatic conditions, such as deep groundwater, may be depleted in these stable isotopes and reflect a more negative isotope composition [11,105,111,112].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The water temperature is relatively high; in the summer it can reach the 26–28°C. The water has considerably high pH as well (7.8–9.2) and contains a high concentration (1–3 g/L) of dissolved salts (mainly Na- and Mg-hydrogen-carbonates and sulphates) [ 26 , 27 ]. The sampling took place in a public area, and no permission was required for collecting water samples.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Tandel et al [42] experimentally confirmed that S. australis could not grow at temperatures below +7˚C, whereas S. parasitica could tolerate a wider range of temperatures (+4-20˚C). Meanwhile, other studies have found that decreasing water depth and higher water temperatures favour bacteria which can suppress the growth of water mold, suggesting that water temperature only plays an indirect role in regulating water mold abundance [11,26]. Besides water temperature and salinity, the human factor should also be considered.…”
Section: Plos Onementioning
confidence: 99%